2003
DOI: 10.1152/japplphysiol.01171.2002
|View full text |Cite
|
Sign up to set email alerts
|

Muscle creatine uptake and creatine transporter expression in response to creatine supplementation and depletion

Abstract: The total creatine pool size [Crtotal; creatine (Cr) + phosphocreatine (PCr)] is crucial for optimal energy utilization in skeletal muscle, especially at the onset of exercise and during intense contractions. The Crtotal likely is controlled by long-term modulation of Cr uptake via the sodium-dependent Cr transporter (CrT). To test this hypothesis, adult male Sprague-Dawley rats were fed 1% Cr, their muscle Crtotal was reduced by ∼85% [1% β-guanidinoproprionic acid (β-GPA)], or their muscle Crtotal was replete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 46 publications
1
22
0
1
Order By: Relevance
“…Since a 1% increase in TCr with 11% labeled Cr would result in a 10% increase in TCr signal intensity, this indicates that the absolute increase in Cr concentration in the skeletal muscle of our volunteer was somewhat low (1% ± 3%; i.e., (81–70%)/10). Personal factors, including fiber‐type distribution (5, 25), the starting Cr concentration (9), age (19, 26), the so‐called “responsiveness” of the subject (27), and the skeletal muscle examined (11, 12, 28, 29) may all play a role in Cr uptake (see also Ref 3. and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…Since a 1% increase in TCr with 11% labeled Cr would result in a 10% increase in TCr signal intensity, this indicates that the absolute increase in Cr concentration in the skeletal muscle of our volunteer was somewhat low (1% ± 3%; i.e., (81–70%)/10). Personal factors, including fiber‐type distribution (5, 25), the starting Cr concentration (9), age (19, 26), the so‐called “responsiveness” of the subject (27), and the skeletal muscle examined (11, 12, 28, 29) may all play a role in Cr uptake (see also Ref 3. and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence that AMPK activation is regulated by phosphorylation of the AMPK ␣-subunit by upstream kinases (AMP kinase kinase) (13,29,30) in total creatine in skeletal muscle over 7 wk of creatine feeding (4). Interestingly, despite no changes in intracellular [creatine], increases in plasma [creatine], and no change in creatine transporter abundance, creatine uptake rates were lowered by ϳ50% in white muscle after the 7 wk of creatine feeding (4). This suggests that, during creatine feeding, some factor other than tissue total creatine content can affect muscle physiology.…”
Section: Discussionmentioning
confidence: 99%
“…After creatine supplementation the levels of TCr were similar in both strains (Table 1): TCr increased by 12% in muscles of mdx mice and remained unchanged in C57 animals. A lack of TCr increase in EDL muscle of C57 mice has been reported previously 4, 7, 23. Recently, Brault et al4 showed that, after creatine depletion by guanidinopropionic acid (GPA), the rate of creatine uptake was related to fiber type and independent of the level of creatine reached.…”
Section: Discussionmentioning
confidence: 77%